Hard Knocks : Domestic Violence and the Psychology of Storytelling. - Haaken, Jan (Women and psychology., 2010)
Shows how cultural contexts shape how stories about domestic abuse get told, and offers tools for bringing psychology into discussions of group dynamics in the domestic violence field. This book explores the contentious issue of how to acknowledge forms of female aggression while still preserving a gender analysis of intimate partner violence.